Effects of Water Quality on the Growth, Molting and Mortality Of Mud Crab, Scylla Serrata Forskal (Decapoda: Portunidae) From Cox’s Bazar (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The important decapod crustacean, the soft-shell crab, Scylla serrata is in great demand in different countries due to its taste next to shrimp and nutritional value, for which its farm is growing day by day as a source of income generation. This experiment was conducted for one year from January 2016 to December 2016 in Chaufaldandi, Cox’s Bazar, Bangladesh to study the growth, molting and mortality rates of the soft shell crab and water quality of the crab culture pond. During the three experiments in a year, matured male crab showed highest growth performance (28.00±7.02g to 32.15±3.87g). Mature female crab showed maximum molting (60%) during the 3rd experimental period (September to December), while immature crab depicted the highest rate of molting (75%) in the 2nd (May-August) and 3rd experimental periods (September- December). Mortality rate was found highest in mature male during the 1st experimental period (60%). The female crab showed maximum mortality rate (40%) during the 1st experimental period. The survival rate was best for female and immature S. serrata. The growth of S. serrata showed significant positive relationships with water temperature, salinity, water pH, soil pH, and alkalinity during the all three experimental periods. The 2nd and 3rd experimental periods were found to be the most favorable time to produce soft-shell crab due to suitable weather conditions.J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 25-36